Peranan Lembaga Keuangan Mikro Berbasis Teknologi Informasi dalam Mengembangkan Usaha Mikro - Nazwirman Nazwirman (The Winners, 2008)
The effort to develop globally competitive Micro Business needs an Information Technology to fulfill the needs of the said business. This is to ease the administration system of the Micro Business, fast in service, easy to develop product and easy to gain trust from financial institutions. Information Technology implementation in a micro financial institution is important to develop itself. Information technology of a Micro Financial Institution will enable to professionalize a company and is committed to give the best Information Technology products and services for Micro Financial Institution, not only in Indonesia but also in the world. Thus, competitive advantage such as experience, competence (specialization), after-sales, and product quality from micro financial institution is attained.